REVIEW OF THE INORGANIC GEOCHEMISTRY OF PEATS AND PEATLAND WATERS - Shotyk W. (My University, 1988)
The major floristic and geochemical differences between bogs, fens, and swamps are summarized, and the most common peat types described. This is followed by a critical, historical review of the literature.The methods used to measure the pH of peatland (mire) waters are examined, and the pH range of various peatland types is reported. In addition, horizontal and vertical pH variations are illustrated, and factors affecting the pH of these waters reviewed. The cause of the low pH of surface waters of Sphagnum bogs (approximately pH 4) is critically investigated, and the relative importance of dissolved CO2 and other inorganic acids, and organic acids to the low pH is assessed. Cation exchange on the surfaces of Sphagnum mosses is found to be a relatively unimportant acidification mechanism, but important to the chemical ecology of the plants.The redox chemistry of mire waters is described in terms of the geochemistry of such redox indicators as O2, CO2, CH4, CO, H2, H2S, SO42−, native Cu, and siderite (FeCO3). Published studies of Eh in peatlands are cited, and the problems of Eh measurement and interpretation are explored.The chemical composition of mire waters (major and trace metals, and nonmetallic species) is examined, and factors affecting their composition reported.The abundance and distribution of mineral matter in peats is described, and the occurrence and formation of minerals of Fe (pyrite and other sulphides, siderite, vivianite), Cu (chalcopyrite, native Cu, covellite) and Zn (smithsonite and wurtzite) investigated. The abundance and distribution of major elements (Si, Al, Na, K, Mg, Ca) and trace metals (Ni, V, Cr, Fe, Mn, Cu, U, Zn, Pb) is described, and factors affecting their solubility examined.